2006
DOI: 10.1124/mol.106.026237
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Regulates Adrenergic Expression

Abstract: The mechanism by which nerve growth factor (NGF) regulates adrenergic expression was examined in PC-12 cells transfected with a rat phenylethanolamine N-methyl-transferase (PNMT) promoter-luciferase reporter gene construct pGL3RP893. NGF treatment increased PNMT promoter-driven luciferase activity in a dose-and time-dependent manner. Induction was attenuated by inhibition of the extracellular signalregulated kinase mitogen-activated protein kinase (MAPK) pathway (ϳ60%) but not by inhibition of the protein kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 57 publications
1
10
0
1
Order By: Relevance
“…Indeed, EGR1 was dramatically recruited into the nucleus when induced by NGF in PC12 cells, as demonstrated by Western blot analysis ( Figure 1D) and EMSA (Supplementary Figure S1 at http://www.BiochemJ.org/bj/440/bj4400273add.htm). These results are consistent with those reported previously [33]. Thus we deduced that the NGF induction of heparanase in PC12 cells was likely to be mediated by the TrkA-EGR1 pathway.…”
Section: Ngf-induced Heparanase Expression In Pc12 Cells Is Attenuatesupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, EGR1 was dramatically recruited into the nucleus when induced by NGF in PC12 cells, as demonstrated by Western blot analysis ( Figure 1D) and EMSA (Supplementary Figure S1 at http://www.BiochemJ.org/bj/440/bj4400273add.htm). These results are consistent with those reported previously [33]. Thus we deduced that the NGF induction of heparanase in PC12 cells was likely to be mediated by the TrkA-EGR1 pathway.…”
Section: Ngf-induced Heparanase Expression In Pc12 Cells Is Attenuatesupporting
confidence: 93%
“…Nuclear extracts (NE) isolated from PC-12 cells exposed to NGF for 60 and 120 min were subjected to EMSA using 32 P-labelled double-stranded oligonucleotides encoding the EGR-1-binding element in the PNMT promoter (5 -CCTCCCGCCCCCGCGCGTCC-3 ) as a probe as described previously [33]. Protein-DNA complexes after separation on 5 % polyacrylamide gels were visualized by autoradiography.…”
Section: Author Contributionmentioning
confidence: 99%
“…In studies using PC12 cells that are widely used for examining NGF, others have shown that NGF increases the expression of certain genes by augmenting DNA binding or activity of transcription factors such as Sp1, c-fos, c-jun, Egr-1, and STAT3 etc. (Pierchala et al, 2004;Sobue et al, 2005;Ng et al, 2006;Pelligrino and Stork, 2006;Rojo et al, 2006;Tai et al, 2006). NGF signal is transduced through various pathways to activate transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory cells or exposed nerves produce and release NGF, and the elevated circulating NGF regulates the conversion of chromaffin cells to neurons through upregulating p-ERK-JMJD3-Mash1 signaling and regulating peripherin and adrenergic expression via posttranscriptional control of the PNMT gene (29). The neuronal transition may provoke alternations in the morphology and function of AMCC, which reduce the baseline and stress-induced EPI levels and subsequently cause the ineffective dilatation of the bronchi.…”
Section: L608 Adrenal Medulla Cells Conversion In Eibmentioning
confidence: 99%